Analisis Pengendalian Keterlambatan Pembayaran Piutang Dari Pelanggan - Amando Purba (JEMA: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
Trade receivables are an important asset in company financial reporting, especially for PT DNR Distribution Medan Branch which operates in the field of credit sales of pharmaceutical products. However, this credit system carries the risk of late payments, disrupting cash flow, increasing collection costs, and potentially causing losses if receivables are not collected. This study aims to analyze the factors that cause late payments of accounts receivable and the management strategies implemented by companies. The research methodology used is qualitative with a descriptive approach. Data collection was done through interviews and literature review and data analysis was done using descriptive method, i.e. by writing down and processing the data into understandable text. Research found that late payments of accounts receivable are caused not only by internal factors such as clerical errors and bottlenecks in the collection process, but also by external factors such as delays in the disbursement of funds from certain institutions.. PT DNR Distribution Medan Branch has implemented the SAP system to manage its receivables, but still faces challenges in ensuring customers pay on time. Therefore, a more effective management strategy is needed, including improving the billing system, evaluating credit policies, and a more proactive approach in monitoring customers. With the right strategy, businesses can minimize payment delays and optimize receivables management.